Patriarchy and the Regulation of Feminity in Edo Japan: A Foucauldian Discourse Analysis - Nina Alia Ariefa (Chi e Journal of Japanese Learning and Teaching, 2025)
Literary works serve as cultural instruments that reflect and perpetuate dominant social ideologies, including those related to gender and power. This study investigates the construction of women’s discourse during the Edo period (1603–1868), a feudal era under Tokugawa rule, through a Foucauldian analysis of Shinjū Tenno Amijima, one of the most prominent plays of the time. Using Foucault’s theory of discourse and a qualitative discourse-analytical approach, the research examines how female subjectivity is represented, regulated, and disciplined within the text. The findings reveal that portrayals of women’s self-sacrifice, emotional restraint, and loyalty to men function as mechanisms of social control that reproduce patriarchal values. These depictions naturalize women’s subordination and reinforce gendered hierarchies within Edo society. The study further argues that discourse in Shinjū Tenno Amijima operates as a form of power—one that shapes gender norms and legitimizes women’s roles within the sociocultural structure of the period. By situating literary representation within the broader framework of Foucauldian discourse theory, this research contributes to understanding how literature not only mirrors but also sustains systems of power and patriarchy in premodern Japan.